(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper presents a novel shunt active power filter (Shunt APF) system based on a nine-level neutral point clamped (NPC) inverter, which can reduce current harmonics under various nonlinear loads. These loads can introduce harmonic currents within the system, which causes excessive power losses and alters the voltage systems’ characteristics. Today, multi-level inverters are more suitable for high-voltage applications; their advantages are low harmonic distortions, low switching losses, low electromagnetic interference, and low acoustic noise. The reference signals required to compensate harmonic currents use the synchronous detection method (SDM) with phase disposition sinusoidal pulse width modulation (PD-SPWM) control due to its low complexity and superior performance. The proposed shunt APF configuration simulation is evaluated using MATLAB-Simulink and SimPowerSystem environment with inductive and capacitive non-linear loads. The simulation results show the efficiency of the proposed shunt APF in terms of harmonic compensation and power quality improvement. The results of comparative studies with other less multi-level inverters confirm the superiority of the proposed shunt APF system.